The Theory of Significant Learning and the teaching of Atomic Orbitals: A systematic review of the literature (Research, Society and Development, 2022)
Several theorists have reported difficulties presented by students regarding the study of Atomic Orbitals, from a mistaken conceptual understanding to a difficulty in spatial visualization. The study of this topic from the principles of significant learning can enhance the conceptual construction by the student, since it facilitates the retention of information in their cognitive structure. The present work is a Systematic Review of Literature (SRL) in several databases that encompass the scope of Chemistry, with a time frame between the years 2016 to 2022, with the objective of finding approaches to the theme Atomic Orbitals from the theory of ausubelian learning. The selected works were categorized based on a content analysis, and the results showed that this is a line of research that lacks studies, since the theme of Orbitals is essential for the student to develop an understanding of the structure of the subject, chemical bonds and the properties of substances.